Spacers in the treatment of hip joint infections: numerical analysis of their durability - Weiss, Brenda Anahí (2013)
Hip spacers are temporary implants having a geometry similar to the femoral component of a hip prosthesis, and they are manufactured with antibiotic-impregnated bone cement. The use of spacers in two stage revisions is the most effective treatment to eradicate infections and to avoid limb shortening. The most frequent complication associated with spacers is fatigue failure, for which doctors recommend patients to stay at rest. In this work, several spacer designs are analyzed in order to determine the feasibility of doing activities like walking, standing up or sitting down while performing the antibiotics treatment. Designs combine both different neck diameters and the presence/absence of an internal, stainless steel reinforcement. By means of computational simulations based on the finite element method, stress fields are calculated for various hip spacer designs under several load and fixing conditions. For this purpose, a 3D model of human femur is generated by processing tomographic images with segmentation techniques and inverse engineering. The results allow us to estimate the life expectancy of each design, by considering the fatigue behavior of the bone cement. Only the introduction of a reinforcement with a proper diameter into the bone cement matrix could assure the integrity of the spacer along the treatment period.